Monomial size vs. Bit-complexity in Sums-of-Squares and Polynomial Calculus - Hakoniemi, Tuomas (Proceedings of the 36th Annual ACM/IEEE Symposium on Logic in Computer Science, 2021)
In this paper we consider the relationship between monomial-size and bit-complexity in Sums-of-Squares (SOS) in Polynomial Calculus Resolution over rationals ({\text{PCR}}/\mathbb{Q}). We show that there is a set of polynomial constraints Q n over Boolean variables that has both SOS and {\text{PCR}}/\mathbb{Q} refutations of degree 2 and thus with only polynomially many monomials, but for which any SOS or {\text{PCR}}/\mathbb{Q} refutation must have exponential bit-complexity, when the rational coefficients are represented with their reduced fractions written in binary.